Redes dinâmicas de sensores sem fio ZigBee para aplicações de monitoramento e controle - Oliveira, Thiago de Almeida [UNESP] (2015)
The wireless sensor network (WSN) technology has attracted increasing attention considering its potential in many application fields. In most studies on WSNs, the network is assumed to cover a large number of static devices over a fixed coverage area. As an extension of WSN capacibilities, the devices mobility and network dynamism provide a new chain of interesting applications defined as Wirelles Dynamic Sensor Network (WDSN). The initial challenge in WDSN is to investigate whether this dynamic imposed on the network will be supported, once the used network protocol must meet the requirements for WDSN applications such as network formation and self-organization, communication management with the input and output devices on the network, route discovery and data transmission with node mobility, among other characteristics. In order to overcome these issues, specific wireless protocols have been developed to meet applications with devices mobility in WSN. However, these specific protocols limit the development of WSN since they are isolated and proprietary solutions, instead of using a standardized protocol for interoperability. In this context, this work presents a feasibility analysis of ZigBee protocol for WDSN applications. A survey of application features and requirements, as well as a discussion of advantages and limitations, regarding adoption of the ZigBee protocol in WDSN are presented. A design and development methodology of ZigBee WDSN is proposed in order to assist in new applications of this technology. Furthermore, an experimental validation using ZigBee protocol devices proves the WDSN potential